2012
DOI: 10.2214/ajr.12.8798
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association Between Superolateral Hoffa Fat Pad Edema on MRI and Clinical Evidence of Fat Pad Impingement?

Abstract: Edema is present on MRI in the superolateral region of Hoffa fat pad in patients with clinical fat pad impingement. However, such edema can also be present in patients without symptoms of fat pad impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…65 Young patients are most prone to superolateral Hoffa fat pad edema and such edema may be asymptomatic. 68 Anterolateral pain has also been found most often to be associated with tendinosis of the lateral patellar tendon in the setting of superolateral IPFP impingement.…”
Section: Ipfp Of Hoffamentioning
confidence: 99%
“…65 Young patients are most prone to superolateral Hoffa fat pad edema and such edema may be asymptomatic. 68 Anterolateral pain has also been found most often to be associated with tendinosis of the lateral patellar tendon in the setting of superolateral IPFP impingement.…”
Section: Ipfp Of Hoffamentioning
confidence: 99%
“…On MR imaging, superolateral fat pad oedema appears to be a sensitive but non-specific sign for PT-LFCFS. In a study by De Smet et al, (7) this finding was present in all clinically symptomatic patients, although it was also seen in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 74%
“…The literature is unclear regarding the prevalence of SHFP edema in general population as judged by selection of case patients in various studies, which ranges from 4% to 50%. 7-9, 11 Subhawong et al 7 retrospectively reviewed the records of 212 patients over a 2-month period. After excluding patients outside the age range of 14 to 50 years, history of trauma, previous surgery, and major internal derangement, they were left with 50 knee MR examinations, of which 50% demonstrated SHFP edema.…”
Section: Discussionmentioning
confidence: 99%
“…This somewhat supports previous studies which suggested high prevalence in general population. 7,11 One of the contributors is sex-related difference in muscle strength, conditioning, and an increased Q angle which accounts for higher prevalence of patellar maltracking in females. Excessive stresses associated with abnormal patellofemoral joint mechanics are seen more commonly in young girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation